PENGARUH E-LKPD BERBASIS LAPS-HEURISTIC BERBANTUAN LIVEWORKSHEETS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Wilda Astuti; Oktaviana Nirmala Purba (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study was conducted to examine the effect of using LAPS Heuristic-basedE-LKPD on students’ learning outcomes. The research applied a quantitative approachwith a pretest-posttest design. The sample of this study consisted of 36 students. Datawere collected through a pretest administered before the implementation of the E-LKPDand a posttest conducted after the implementation of the LAPS Heuristic-based E-LKPD.The obtained data were analyzed using a paired sample t-test to determine the differencesin learning outcomes before and after the treatment. The findings revealed that theaverage pretest score was 69.36, while the average posttest score increased to 92.47. Thestatistical analysis showed that the value of ???????????????????????? = 14.37, whereas the value of???????????????????????? = 2.03at the 5% significance level. Since the value of ????????????????????????was higher than????????????????????????, H₀ was rejected and H₁ was accepted. These results indicate that the use of LAPSHeuristic-based E-LKPD had a significant effect on improving students’ learningoutcomes. Therefore, the LAPS Heuristic-based E-LKPD was considered effective for usein the learning process.